Carry me home - Fox, Janet S. (Simon & Schuster Books for Young Readers, 2022)
Twelve-year-old Lulu, burdened with caring for her sister, Serena, since their father disappeared, must learn to trust her new friends and community when secrets and lies catch up with her.